Minimally Invasive Surgery for Pediatric Tumors – Current State of the Art - Fuchs, Jörg; Schafbuch, Luana; Ebinger, Martin; Schäfer, Jürgen F.; Seitz, Guido; Warmann, Steven W. (Frontiers in Pediatrics, 2014)
During recent years minimally invasive surgery (MIS) has become the standard approach for various operations in infants and children. This also holds true for surgery in children with solid tumors. Meanwhile, more and more oncological biopsies and resections are being performed laparoscopically or thoracoscopically. Despite its increasing role in pediatric tumor surgery, the different national and international multicenter trial groups have not yet implemented MIS within guidelines and recommendations in most of the current treatment protocols. An increasing number of reports describe a potential role of MIS in the different entities of pediatric surgical oncology. Over the time, there has been a diverse development of this approach with regard to the different neoplasms. The aim of this article is to give an overview and to describe the current state of the art of MIS in pediatric solid tumors.